Icy ocean worlds - astrobiology research in Germany - Klenner, Fabian; Baqué, Mickael; Beblo-Vranesevic, Kristina; Bönigk, Janine; Boxberg, Marc S.; Dachwald, Bernd; Digel, Ilya; Elsaesser, Andreas; Espe, Clemens; Funke, Oliver; Hauber, Ernst; Heinen, Dirk; et al. (Frontiers in Astronomy and Space Sciences, 2024)
Icy bodies with subsurface oceans are a prime target for astrobiology investigations, with an increasing number of scientists participating in the planning, development, and realization of space missions to these worlds. Within Germany, the Ocean Worlds and Icy Moons working group of the German Astrobiology Society provides an invaluable platform for scientists and engineers from universities and other organizations with a passion for icy ocean worlds to share knowledge and start collaborations. We here present an overview about astrobiology research activities related to icy ocean worlds conducted either in Germany or in strong collaboration with scientists in Germany. With recent developments, Germany offers itself as a partner to contribute to icy ocean world missions.